2018
DOI: 10.1039/c8ra03174f
|View full text |Cite
|
Sign up to set email alerts
|

Accessing new 2D semiconductors with optical band gap: synthesis of iron-intercalated titanium diselenide thin films via LPCVD

Abstract: Fe-doped TiSe2 thin-films were synthesized via low pressure chemical vapor deposition (LPCVD) of a single source precursor: [Fe(η5-C5H4Se)2Ti(η5-C5H5)2]2 (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Ge et al synthesized TiSe 2 chemically and obtained the bandgap of 1.44 to 1.51 eV after photodegradation for 10 to 120 min respectively, measured using diffused reflectance spectroscopy . Sanchez et al have also reported a bandgap of 1.46 eV after Fe intercalation in TiSe 2 ; however, they have not mentioned about the “pristine” bandgap value from their experiment . This bandgap falls close to the Shockley–Queisser limit for maximum solar energy conversion efficiency in solar cell application.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ge et al synthesized TiSe 2 chemically and obtained the bandgap of 1.44 to 1.51 eV after photodegradation for 10 to 120 min respectively, measured using diffused reflectance spectroscopy . Sanchez et al have also reported a bandgap of 1.46 eV after Fe intercalation in TiSe 2 ; however, they have not mentioned about the “pristine” bandgap value from their experiment . This bandgap falls close to the Shockley–Queisser limit for maximum solar energy conversion efficiency in solar cell application.…”
Section: Resultsmentioning
confidence: 99%
“…It witnesses that the intrinsic defects or disorder in TiSe 2 can increase the bandgap along with short-range CDW, which is suitable for tunable multifunctional advanced materials for extensive application. Many examples show that 2D materials exhibit highly tunable bandgaps, realized via the control of the number of layers, heterostructuring, strain engineering, chemical doping, alloying, intercalation, substrate engineering, and an external electric field. , Unlike conventional semiconductors, 2D materials are in their polymorphic nature, allowing for vastly different band structures and electronic properties in various phases, which is useful for transistor Ohmic contacts for exotic quantum behavior like spin-valley and Weyl Fermion physics and realizing memristive devices . It should be noted that the photoemission measurements are always on the cleaved single crystal or exfoliated clean defect-free TiSe 2 layers.…”
Section: Resultsmentioning
confidence: 99%
“…Following our previous work on Fe x TiSe 2 thin films via LPCVD from the single-source precursor [Fe­(η 5 -C 5 H 4 Se) 2 Ti­(η 5 -C 5 H 5 ) 2 ] 2 , Fe x ZrSe 2 thin film synthesis from [Fe­(η 5 -C 5 H 4 Se) 2 Zr­(η 5 -C 5 H 5 ) 2 ] 2 ( 1 ) (Figure a) was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Low-pressure chemical vapor deposition (LPCVD) of organometallic precursors appears to be a suitable alternative due to its versatility toward the use of alternative air/moisture-sensitive precursors. This method allows growth of high-quality thin films from volatile, temperature-sensitive reagents and has been used extensively in the past decade for the synthesis of thin films of functional materials, many of them metal selenides. In the present paper, we investigate the ability of single-source precursor [Fe­(η 5 -C 5 H 4 Se) 2 Zr­(η 5 -C 5 H 5 ) 2 ] 2 ( 1 ) to successfully generate thin films of Fe-intercalated ZrSe 2 (i.e., Fe x ZrSe 2 ) using a convenient single-step deposition process via LPCVD and record the optical band gap shift resultant from the intercalation.…”
Section: Introductionmentioning
confidence: 99%
“…N-functionalized piperazine and morpholine molecules have promising pharmacological activity and therapeutic application. 39 Catalytic methodology was used for the synthesis of dibenzylpiperazine and 1-(4-morpholinophenyl)-3-phenylprop-2-en-1-one. Both of these molecules are obtained in excellent yields (Schemes 2 and 3).…”
Section: Substrate Scopementioning
confidence: 99%